Pendampingan Psikososial Santri Berbasis Nilai Kepesantrenan: Studi Implementasi Program Psikoedukasi & Konseling di Pondok Pesantren Tebuireng - Intan Nur Fauziah Saputri; Habibatul Qudsiyyah; M. Adla Mudafi; Muhammad Nuril Huda; Muhammad Reyhan Dzakwan; Syifa Alistya Sevita Putri; Siti Muti’atul Hasanah; Thalita Nur Shobiroh; Adhimah Lailiyah; Sayidatul Aisah; Moh. Yasyfa Anjana; Muhammad Quthbil Haikaly Abil Hasan A (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2026)
In the world of Islamic boarding schools, every student faces various psychosocial problems related to social adaptation, academic pressure, and religious discipline. This condition requires contextual psychosocial support in accordance with the values of Islamic boarding schools. This study aims to determine how psychoeducation and counseling programs are implemented at an Islamic boarding school called Pondok Pesantren Tebuireng. This study is a qualitative case study. Information was collected through participatory observation, in-depth interviews with students, counselors, and boarding school program supervisors, as well as documentation of program activities. The results of the study indicate that psychoeducation and counseling programs based on boarding school values can increase mental health awareness, emotional regulation, and the willingness of adult students to communicate their psychosocial problems to others. Therefore, the conclusion of this study shows that psychoeducation and counseling conducted in Islamic boarding schools are effective and sustainable support models that should be implemented to enable the psychological well-being of students.